Motilitas dan Abnormalitas Spermatozoa X dan Y Kambing Lokal pada Berbagai Persentase Gradient Percoll Menggunakan Metode Swim Down - Teguh Ari Prabowo; Sugiyatno Sugiyatno (Musamus Journal of Livestock Science, 2021)
The purpose of this study was to determine the quality of spermatozoa X and Y from semen of domestic goat which separated with various concentration of percoll. The metode of this study is experimental laboratory. The treatment consist of several concentration of percoll and diluter of percoll. R1 treated by 30% percoll : 70% diluter, R2 treated by 40% percoll : 70% diluter, R3 treated by 50% percoll : 70% diluter, and R4 treated by 60% percoll : 70% diluter. Experimental disign used in this experimental was RCBD (Randomize Complete Block Disain). Each treatment was replicated six times with the size of circle scrotum as the block. Result showed that the treatment R1 for X and Ybearing sperm, sperm motility, was 77,50 ± 5,00 and 70,00 ± 14,14, sperm abnormality was 10,50 ± 1,52 and 8,91 ± 1,31. The treatment R2 for X and Y-bearing sperm, sperm motility and sperm abnormality was 75,00 ± 5,77, and 75,00 ± 5,77, abnormality was 10,44 ± 1,09 and 11,4 ± 1,47. The treatment R3 for X and Y-bearing sperm, sperm motility was and sperm abnormality was 67,5 ± 5,00 and 62,50 ± 5,00, abnormality was 8,07 ± 1,40 and 9,37 ± 1,35. The treatment R4 for X and Y-bearing sperm, sperm motility, and sperm abnormality was 72,50 ± 9,57 and 60,00 ± 8,16, abnormality was 10,87 ± 2,84 and 9,83 ± 2,20. Sperm separation with the different concentration of percoll were hightly significant (P < 0.01) to identify spermatozoa X and Y chromosome, but there was no significantly different (P > 0.05) in the sperm motility and sperm abnormality. It is concluded that semen selected by variouse concentration of percoll and diluter increased the presentage of X and Y-bearing sperm. However motility and abnormality of X and Y-bearing sperm were not affected by the treatment.